The Influence of Proftiability, Leverage, and Corporate Social Responsibility on Tax Avoidance (Study on Energy Companies Listed on Idx) - Agassi, Reza; Djamhuri, Ali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study examines the influence of profitability, leverage, and corporate social responsibility (CSR) on tax avoidance among 15 energy companies listed on the Indonesian Stock Exchange (IDX) from 2019 to 2022. Employing Agency Theory as a theoretical framework, the study aims to determine the individual and combined influences of these variables on tax avoidance, using key financial ratios such as Return on Assets (ROA), Debt-to-Equity Ratio (DER), and the Corporate Social Responsibility Disclosure Index (CSRDI). The findings reveal that both leverage and CSR exhibit a significant positive influence on tax avoidance practices, whereas the influence of ROA on tax avoidance is not statistically significant. This observation is potentially attributed to the unique circumstances during the COVID-19 era, which could have disrupted the influence between profitability and tax avoidance. However, when profitability, leverage, and CSR are considered together, their combined influence on tax avoidance is significant. These insights shed light on the complex dynamics at play in tax strategies within the energy sector. As a future research consideration, it is recommended to revisit this study post-COVID-19, allowing for a more stable economic environment. This may yield different results and further clarify the intricate interplay between profitability, leverage, CSR, and tax avoidance in the energy sector. Abstrak Penelitian ini menguji pengaruh antara profitabilitas, leverage, dan tanggung jawab sosial perusahaan (CSR) terhadap penghindaran pajak pada 15 perusahaan energi yang terdaftar di Bursa Efek Indonesia (BEI) dari tahun 2019- 2022. Menggunakan Teori Agensi sebagai kerangka toeri, penelitian ini bertujuan untuk menentukan pengaruh individual dan gabungan dari variabel-variable ini terhadap peghindaran pajak dengan menggunakan rasio keuangan seperti Return on Assets (ROA), Debt-to-Equity Ratio (DER), dan Corporate social Responsibility Disclosure Index (CSRDI). Temuan menunjukkan bahwa leverage dan CSR menunjukkan pengaruh positif yang signifikan terhadap praktik penghindaran pajak, sedangkan pengaruh ROA terhadap penghindaran pajak tidak signifikan secara statistik. Pengamatan ini berpotensi dikaitkan dengan keadaan unik di era COVID-19, yang dapat mengganggu pengaruh antara profitabilitas dan penghindaran pajak. Namun, ketika profitabilitas, leverage, dan CSR dipertimbangkan bersama-sama, pengaruh gabungan keduanya terhadap penghindaran pajak menjadi signifikan. Pemahaman ini menjelaskan dinamika kompleks yang berperan dalam strategi perpajakan di sektor energi. Sebagai pertimbangan penelitian di masa depan, disarankan untuk meninjau kembali penelitian ini pasca-COVID-19, sehingga memungkinkan lingkungan ekonomi yang lebih stabil. Hal ini mungkin memberikan hasil yang berbeda dan semakin memperjelas interaksi yang rumit antara profitabilitas, leverage, CSR, dan penghindaran pajak di sektor energi.